Simplified radar architecture based on information metasurface - Si Ran Wang; Zhan Ye Chen; Shao Nan Chen; Jun Yan Dai; Jun Wei Zhang; Zhen Jie Qi; Li Jie Wu; Meng Ke Sun; Qun Yan Zhou; Hui Dong Li; Zhang Jie Luo; Qiang Cheng; et al. (Nature Communications)
Abstract Modern radar typically employs a chain radio-frequency (RF)-digital architecture, imposing high costs, substantial hardware burdens, and integration challenges. Here, we propose a simplified radar architecture based on space-time-coding (STC) information metasurfaces. With the capabilities to generate multiple frequencies and customize their phases, the STC metasurfaces play crucial roles in both transmission and reception: they enable chirp signal generation and radiation at the transmitter while facilitating echo reception and dechirp processing at the receiver. Remarkably, dechirp processing is performed at the RF level, removing the need for high-speed digitization and potentially enabling more efficient signal processing than conventional digital methods. As a proof of concept, experiments demonstrate that the proposed metasurface radar achieves target detection and range/speed measurement performance comparable to that of conventional systems. This study presents an innovative radar system paradigm that integrates RF front ends and signal processors onto an information metasurface platform, achieving essential sensing functions with reduced system complexity and cost.